GAMBARAN KESESUAIAN SURAT PESANAN DENGAN FAKTUR DATANG DI APOTEK - Bayu Dwi Handono; Guruh Subagya; Alifa Sabrina; Meri Oliviana Dewi (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2023)
Emptiness of drugs in pharmacies causes losses, including negligence, medication errors, delayed treatment, and causing patient complaints. One of the factors that can be a factor in the occurrence of drug vacancies is the distribution of drugs by PBF that exceeds the lead time, the number of orders that are not in accordance with the order letter, the number of items delivery did not fulfill the order letter. And another factor is, errors in drug receipt or distribution by PBF result in a return process which causes inefficiency in services to patients who come. This study aims to find out the description of the suitability of the order letter with the incoming invoice at the X Pharmacy, Depok, West Java. The method used in this research is descriptive method with retrospective data collection which is based on tracking documents and incoming invoices. Data collection is done by looking at the suitability of the order letter and incoming invoice which consists of the suitability of the name of the drug preparation, the form of the drug dosage form, the strength of the drug preparation, the contents of the package, the number of peritem drugs and the number of drugs per item arrived. The research sample was taken using a total sampling technique at the X Pharmacy in January-March 2021. Overall, in this study, 180 orders and 292 invoices arrived. The results showed that in January the percentage of conformity of the order letter with the incoming invoice was 48.78%, in February the percentage of conformity was 57.89%, in March the percentage of conformity was 59.76%. The highest percentage of conformity is in March 2021 with a percentage of 59.76%. The average percentage of correspondence between orders and invoices during January - March 2021 is 55.47%.